Analisis Risiko Text Next Syndrome Pada Pemain Game Smartphone (Studi Kasus : Mahasiswa Teknik Industri Fakultas Teknik Universitas Mulawarman) - Aditiya Ikhwanudin; Theresia Amelia Pawitra (Jurnal Industri Samudra, 2025)
The use of smartphones for gaming among university students is increasing and often carried out for long durations with poor ergonomic posture. This condition has the potential to cause musculoskeletal disorders, one of which is Text Neck Syndrome (TNS), characterized by neck pain and disability due to excessive forward head flexion. This study aimed to analyze the risk of TNS among Industrial Engineering students at Mulawarman University who play smartphone games and to identify the relationship between screen time and playing posture with the level of neck disability. This research employed a quantitative design with a descriptive analytic approach. The study population consisted of 265 active students from the 2020–2024 cohorts. The sample was determined using purposive sampling, and 50 respondents who met the inclusion criteria were selected. Data were collected using the Neck Disability Index (NDI). Data analysis was performed descriptively and with the Spearman Rank test to examine the relationship between screen time, playing posture, and NDI scores. The results showed that most respondents experienced mild disability (34%), followed by moderate disability (26%), no disability (18%), severe disability (12%), and very severe disability (10%). Respondents with >5 hours of screen time per day had a higher proportion of moderate to severe disability. Moreover, students who played in a cross-legged sitting posture were more likely to experience moderate to very severe disability (63%) compared to those who played while sitting on a chair (44%). In conclusion, university students who play smartphone games are at risk of developing TNS with varying levels of disability, particularly those with longer screen time and cross-legged posture.